2014
DOI: 10.1680/coma.13.00037
|View full text |Cite
|
Sign up to set email alerts
|

China clay waste as aggregate in alkali-activated cement mortars

Abstract: Every 1 t of china clay produced in the UK generates 9 t of waste material. A limited quantity of the coarser waste has beneficial use as a building stone or secondary aggregate in concrete and asphalt, but there are currently limited uses for the finest waste fraction. 'Mica' waste is a mixture of fine minerals and is one of the forms of waste with little beneficial use other than the restoration of old quarries. With an aim to find new commercially viable and low environmental impact uses in construction, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…A significant amount of mining by-product is mica generated both from the mining of relatively valuable materials such as gold, copper, uranium and platinum [13] and that of less valuable materials such as china clay [14] and mica itself [15]. About 10 million tons of mica waste is generated in a year and over 600 million tons of total industry stockpile are estimated to be available [16].…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of mining by-product is mica generated both from the mining of relatively valuable materials such as gold, copper, uranium and platinum [13] and that of less valuable materials such as china clay [14] and mica itself [15]. About 10 million tons of mica waste is generated in a year and over 600 million tons of total industry stockpile are estimated to be available [16].…”
Section: Introductionmentioning
confidence: 99%
“…Within the mining industry, the management of mica waste has generated significant attention due to the large volume generated. Mica waste originates from mining of relatively valuable materials such as gold, copper, uranium and platinum (Nosrati et al, 2009), from mining of coarse material such as granite (Hojamberdiev et al, 2011) from the mining of other phyllosilicates such as China clay (Zografou et al, 2014) and from the mining of mica itself (Basak, 2019). For instance, China clay extraction and processing involves the production of a very large quantity of mica waste, typically for every tonne of china clay, one tonne of residual mica is produced.…”
Section: Introductionmentioning
confidence: 99%
“…Mica waste is usually deposited in large lagoons and abandoned in clay pits. It contains between 10% and 75% mica and currently has seen very limited re-use; within flux for ceramic glazes and as a mild abrasive (Basak, 2019;Hojamberdiev et al, 2011;Zografou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Geopolymers, as known in their generic name, is an alternative to Portland cement with lower CO 2 emissions [10]. A previous paper of this project [11], looking at the performance of the waste in AAC mortar, showed that the increase of the water demand was the main reason for the reduction in the compressive strength of the test mortars using mica and china clay sand. Other authors have looked at the kaolin waste from Brazil with a focus on altering the leftover kaolinite to metakaolin to use it as binder [12][13][14].…”
Section: Introductionmentioning
confidence: 99%